2022
DOI: 10.1002/leap.1496
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and adoption of contributor role ontologies and taxonomies

Abstract: Contributor Role Ontologies and Taxonomies (CROTs) are standard vocabularies to describe individual contributions to a scholarly project or research output. Contributor Roles Taxonomy (CRediT) is one of the most widely used CROTs, and has been adopted by numerous journals to describe author's contributions, and recently formalized as a ANSI/NISO standard. Despite these developments, there is still much work left to be done to improve how CROTs are used across different research domains, research output types, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…There are obviously no studies that explore the use of contributorship statements for other outputs that are not developed yet (e.g., data standards, cohort studies). Furthermore, the logic that guides the development of contributor models is often not made explicit [40]. This raises the question what principles should guide the development of contributor models for any outputs that are not publications, particularly if these models overlap (e.g., datasets $ publications using data).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…There are obviously no studies that explore the use of contributorship statements for other outputs that are not developed yet (e.g., data standards, cohort studies). Furthermore, the logic that guides the development of contributor models is often not made explicit [40]. This raises the question what principles should guide the development of contributor models for any outputs that are not publications, particularly if these models overlap (e.g., datasets $ publications using data).…”
Section: Plos Onementioning
confidence: 99%
“…This raises the question what principles should guide the development of contributor models for any outputs that are not publications, particularly if these models overlap (e.g., datasets $ publications using data). Hosseini et al propose the significant threshold test to identify core roles in contributorship models, which draws on the concepts of indispensability and specificity [40]. They define these dimensions as "so important that research objectives cannot be achieved without them" and "directly associated with the questions and content of research, and constructively affect the reliability, validity and the justification of the reported data, claims, results and conclusions", respectively.…”
Section: Plos Onementioning
confidence: 99%
“…Individuals with anxiety and/or mood disorders are of particular interest as this subpopulation tends to have lower life satisfaction scores compared to those without any mental health disorders (8). Lower life satisfaction in adults with anxiety and/or mood disorders may be at least partially attributed to body dissatisfaction which has been associated with social anxiety disorder and major depressive disorder (9). It has also been found that adults with anxiety and/or mood disorders are more likely to have inaccurate weight perception (10).…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, we also set out to support representation of contributor roles and to make our approach compatible with the Contributor Roles Taxonomy (CRediT), which provides a controlled vocabulary for describing contributions of both authors and non-authors (Holcombe 2019;Brand et al 2015). CRediT is one of several Contributor Role Ontologies and Taxonomies (CROTs), along with the Taxonomy of Digital Research Activities in the Humanities, but is notable for having attracted attention from a broad spectrum of disciplines and has become a National Information Standards Organization standard (at credit.niso.org) (Hosseini, Colomb, et al 2022). One panel of experts with the National Science Foundation has called for journals to require that all contributing authors affirm their contributions as described using this taxonomy in a statement to be published along with the article metadata in order to discourage ghost writing, gift authorship, orphan authorship, and forged authorship (McNutt et al 2018).…”
Section: Introductionmentioning
confidence: 99%